Stuck again? Does the ‘New Cold War’ Impact the Functioning of the UN Security Council? - Stojkovski, Ljupcho (HESTIA, 2024)
The “new Cold War”, which we are now allegedly living through, is not an exact term in international relations. Some observers use it to refer to the renewed tension and animosity between the USA and Russia. Others talk of the looming Cold War-like rivalry between the USA and China, while for many, the concept encompasses the relations between all three major powers. Regardless of these differences of opinion, what is certain is that all three countries are permanent members of the UN Security Council (P3), and if we are indeed living through a second Cold War, this could affect the functioning of the Council as well, which is the international community’s authority for peace and security. During the ‘first’ Cold War, the Security Council was generally dormant and/or blocked by the vetoes of the permanent members, so it is worth investigating whether a similar passiveness and/or ineffectiveness could be expected during the new Cold War. In this paper, it will be argued that while there has been an increased use of vetoes by Russia and China in recent years, a complete paralysis of the Council, like in the past, is not to be expected. Due to the different socio-economic and normative context in which the new Cold War is occurring and in which the Security Council operates, as well as the shared and individual interests that the P3 have in keeping the Council operative, this institution will continue to be functional for most situations that it deals with.
Keywords: Cold War; New Cold War; UN Security Council; UN Security Council (UNSC)